PENGARUH PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY, KEBIJAKAN DIVIDEN, PROFITABILITAS, STRUKTUR MODAL, DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN (Studi pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode 2010-2014) - Nurfina, Hida Efri; Widyarti, Endang Tri (Faculty of Economics and Business Diponegoro University, 2016)
This study aims to test the influence of Corporate Social Responsibility disclosure, dividend policy, profitability, capital structure, and firm size toward firm value which measured by Tobin’s Q. To obtain valid results, the testing performed on each variable based on the hypothesis constructed. The sample used in this study were selected by purposive sampling method. The study population was 135 manufacturing companies listed in Indonesia Stock Exchange. After reduction with several criteria, 19 companies are identified as samples. Observation period is 2010-2014 years, so the number of samples used is 95 sample observations. Testing and analysis method used in this study is multiple regression linear consist of the coefficient of determination test (R2), F statistical test, and t statistical test with classic assumption test such as normality test, multicolinearity test, heteroscedasticity test, and autocorrelation test. The results of this research indicate that Corporate Social Responsibility disclosure has not significant negative effect towards firm value, dividend policy has not significant positive effect towards firm value, profitability and firm size have significant positive effect toward firm value, while capital structure has significant negative effect towards firm value. Profitability has biggest influence towards firm value in this study.